Una estrategia multimodal para mejorar la atención médica de pacientes pediátricos con cáncer y fiebre en Perú - Mendieta, A (2023)
Objective. The DoTT (Decreasing Time to Therapy) project aimed to minimize the interval between fever onset and medical interventions for children with febrile neutropenia. The objective of this study was to determine the effect of implementing the DoTT project on the hospital time to antibiotic (TTA) and patient time to arrival (PTA) at the hospital in children with febrile neutropenia admitted to the emergency department. Methods. The DoTT project was implemented at a Peruvian hospital and followed the World Health Organi‑ zation (WHO) multimodal improvement strategy model. Components included creating a healthcare delivery bundle and antibiotic selection pathways, training users of the bundle and pathways, monitoring patient out‑ comes and obtaining user feedback, encouraging use of the new system, and promoting the integration of DoTT into the institutional culture. Emergency room providers were trained in the care delivery for children with cancer and fever and taught to use the bundle and pathways. DoTT was promoted via pamphlets and posters, with a view to institutionalizing the concept and disseminating it to other hospital services. Results. Admission data for 129 eligible patients in our registry were analyzed. The TTA and PTA were com‑ pared before and after the DoTT intervention. The median TTA was 146 minutes (interquartile range [IQR] 97–265 minutes) before the intervention in 99 patients, and 69 minutes (IQR 50–120 minutes) afterwards in 30 patients (p<0.01). The median PTA was reduced from 1483 minutes at baseline to 660 minutes after the intervention (p<0.01). Conclusions. Applying the WHO multimodal improvement strategy model to the care of children with febrile neutropenia arriving at the hospital had a positive impact on the PTA and TTA, thus potentially increasing the survival of these patients. © 2023 Pan American Health Organization. All rights reserved.